Self-assembled nanoparticles based on amphiphilic chitosan derivative and arginine for oral curcumin delivery - Raja, Mazhar Ali (Int J Nanomedicine, 2016)
Curcumin (Cur) is a striking anticancer agent, but its low aqueous solubility, poor absorption, hasty metabolism, and elimination limit its oral bioavailability and consequently hinder its development as a drug. To redress these limitations, amphiphilic chitosan (CS) conjugate with improved mucoadhesion and solubility over a wider pH range was developed by modification with hydrophobic acrylonitrile (AN) and hydrophilic arginine (Arg); the synthesized conjugate (AN–CS–Arg), which was well characterized by Fourier transform infrared and (1)H nuclear magnetic resonance spectroscopy. Results of critical aggregation concentration revealed that the AN–CS–Arg conjugate had low critical aggregation concentration and was prone to form self-assembled nanoparticles (NPs) in aqueous medium. Cur-encapsulated AN–CS–Arg NPs (AN–CS–Arg/Cur NPs) were developed by a simple sonication method and characterized for the physicochemical parameters such as zeta potential, particle size, and drug encapsulation. The results showed that zeta potential of the prepared NPs was 40.1±2.81 mV and the average size was ~218 nm. A considerable improvement in the aqueous solubility of Cur was observed after encapsulation into AN–CS–Arg/Cur NPs. With the increase in Cur concentration, loading efficiency increased but encapsulation efficiency decreased. The in vitro release profile exhibited sustained release pattern from the AN–CS–Arg/Cur NPs in typical biological buffers. The ex vivo mucoadhesion study revealed that AN–CS–Arg/Cur NPs had greater mucoadhesion than the control CS NPs. Compared with free Cur solution, AN–CS–Arg/Cur NPs showed stronger dose-dependent cytotoxicity against HT-29 cells. In addition, it was observed that cell uptake of AN–CS–Arg/Cur NPs was much higher compared with free Cur. Furthermore, the in vivo pharmacokinetic results in rats demonstrated that the AN–CS–Arg/Cur NPs could remarkably improve the oral bioavailability of Cur. Therefore, the developed AN–CS–Arg/Cur NPs might be a promising nano-candidate for oral delivery of Cur.